Nasopharyngeal Angiofibroma Staging with a Novel Nominal Basis: An 18‐Year Study in a Tertiary Center. (23rd April 2019) - Abdelwahab, Mohamed; Overdevest, Jonathan B.; Elmokadem, Ali; El‐sisi, Hossam; El‐Kholy, Noha Ahmed; Zaki, Hesham; Kamal, Elsharawy; Khafagy, Yasser; Tawfik, Ali; Eldawoody, Hany; Hwang, Peter; Rakha, Abdelwahab
Abstract : Objective: To develop a systematic method for anatomic mapping of juvenile nasopharyngeal angiofibroma (JNA) tumors to standardize communication, facilitate surgical planning, and convey prognosis. Study Design: Retrospective cohort. Setting: Tertiary referral center. Subjects and Methods: Following Institutional Review Board approval, we performed a retrospective review of radiologic and angiographic data of patients with JNA presenting to the Department of Otolaryngology–Head and Neck Surgery, Mansoura University, from 2001 to 2017. All patients underwent angiography with embolization and had >1‐year follow‐up. Based on frequently involved anatomic sites and factors predictive of prognosis, the NSF‐COR staging system (nose/nasopharynx, sinus, fossa‐cranium, orbit, residual internal carotid artery supply) was developed to explicitly convey anatomic site of involvement and presence of residual vascularity. We validated the NSF‐COR staging system against other systems with Pearson chi‐square test based on risk factors and clinical outcomes of blood transfusion volume, recurrence, and JNA resectability. Results: Fifty‐four patients met inclusion criteria, where all primary cases (100%) demonstrated nose/nasopharynx involvement, followed by sinus (85.2%), natural fossae (85.2%), intracranial (26%), and orbital involvement (16.7%). These sites, with assessment of residual internal carotid artery vascular supply, were used to develop the NSF‐COR anatomically based staging system. The components COR showed significant association with clinical outcomes of blood transfusion and recurrence. Contingency coefficients between the NSF‐COR staging system and available staging systems showed significant correlations ( P <. 05) for prognosis. Conclusion: The NSF‐COR staging system conveys a communicable anatomic map of JNA tumors that integrates residual vascularity of the tumor and demonstrates strong concordance with current staging systems to assess clinical outcomes.